Faktor-Faktor yang MempengaruhiPemanfaatan Informasi Akuntansi Pada Usaha Mikro Kecil dan Menengah (UMKM) di Kecamatan Kota Baru Jambi - Wella Wella; Eliyanti Rosmanidar; Khairiyani Khairiyani (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2026)
This thesis aims to determine the effect of length of business, human resources, business scale and religious teachings on the use of accounting information in micro, small and medium enterprises (MSMEs) in Jambi City. This study uses independent variables, namely the length of business, human resources, business scale and religious teachings. The dependent variable is accounting information, the data used in this study is primary data in the form of a questionnaire distributed to 98 MSMEs in Jambi City. This research is descriptive with a quantitative approach. Using multiple regression analysis, class assumption test, t test, f test. The results of this study indicate that the length of business, human resources, scale of business and religious teachings affect the use of accounting information. By using the f test, it is found that the independent variable has a simultaneous influence on the dependent variable. The calculation of the coefficient of determination shows that all independent variables, namely the length of business, human resources, business scale and religious teachings can explain the accounting information variable by 15.7%, the remaining 82.3% is influenced by other variables not examined in this study